Changes in serum levels of autotaxin with direct-acting antiviral therapy in patients with chronic hepatitis C - Yamazaki, Tomoo (PLoS One, 2018)
Sustained virological response (SVR) rates have increased remarkably since the introduction of direct-acting antiviral agents (DAAs) for chronic hepatitis C. Autotaxin (ATX) is a secreted enzyme converting lysophosphatidylcholine to lysophosphatidic acid and a newly established biomarker for liver fibrosis. Interferon-free DAA regimens for chronic hepatitis C could improve liver stiffness in SVR patients according to several non-invasive evaluation methods, but the clinical response and significance of ATX in this context have not yet been defined. We therefore investigated sequential serum ATX levels at baseline, 4 weeks after the start of treatment, and 24 weeks after treatment in 159 hepatitis C virus (HCV)-infected patients who received DAA therapy. Other non-invasive fibrosis markers (aspartate aminotransferase-to-platelet ratio and FIB-4 index) were examined as well. Baseline median ATX levels were comparable between the 144 patients who achieved a SVR and the 15 who did not (1.54 vs. 1.62 mg/L), but median ATX levels became significantly decreased during and after DAA therapy in the SVR group only (from 1.54 to 1.40 and 1.31 mg/L, respectively; P < 0.001). ATX was significantly decreased between baseline and 4 weeks of treatment in overall, male, and female SVR patients (all P < 0.001). In subjects with low necroinflammatory activity in the liver (i.e., alanine aminotransferase < 30 U/L), ATX levels were significantly reduced from baseline to 4 weeks of treatment and remained low (P < 0.001) in patients with a SVR. Thus, interferon-free DAA therapy was associated with a significant decrease in serum ATX levels in patients achieving a SVR, suggesting early regression of liver fibrosis in addition to inflammation treatment.